Augmentation of 3D Holographic Image Graticule With Conventional Microscopy - Askari, Mehdi; Park, Jae-Hyeung (Frontiers in Photonics, 2022)
In this paper, we report an implementation of a computer-generated holographic projection technique to display a holographic scene like a measuring graticule around the magnified sample image in a reflected bright-field microscopy. The implemented system acts as a gauging tool for lateral and longitudinal measurements of a sample that is being observed under a microscope through the assistance of a holographic measuring graticule. Numerical and experimental verifications have been performed, demonstrating the successful augmentation of a holographic projection system as a measuring tool with a conventional bright-field microscopic system.